Correlation between Proper Antibiotics Administration to Community Acquired Pneumonia Patients Based on Alur Gyssens with Clinical Response - Rumende, Cleopas Martin; Chen, Lie Khie; Karuniawati, Anis; Bratanata, Joyce; Falasiva, Rezyta; Sitorus, Truly Panca; Susanto, Erwin Christian (UI Scholars Hub, 2019)
Introduction. The proper of antibiotics treatment will increase the improvement of the patient with community-acquired pneumonia (CAP) and also counteract antimicrobial resistance. Community-Acquired Pneumonia is commonly found in Indonesia with an incidence of 2.4%. This study aimed to determine the proper of antibiotic selection for CAP based on IDSA-ATS 2007 guidelines with Gyssens method and evaluate the relationship between the proper of antibiotic treatment with the clinical response of patients. Methods. A retrospective cohort study was conducted with secondary data from the previous study. Study was conducted in three hospitals in Jakarta, namely Cipto Mangunkusumo General Hospital, Budhi Asih Hospital, and Gatot Subroto Hospital between September 2016 and November 2017. Results. From 151 patients, the appropriate of the first antibiotic treatment, including category 0 and 1 was found in 38 patients (25.2%), while for inappropriate one (category II-V) was in 113 patients (74.8%) mainly due too short antibiotic treatment. For the second antibiotic given to 54 patients, appropriate treatment was found in 15 patients (9.9%). There was no correlation between the accuracy of both antibiotics treatment in CAP based on Gyssens method with clinical response of the patients (first antibiotic treatment: RR=0,970 (95% CI: 0,80 – 1,16), p=0,738; second antibiotic treatment: RR=1,194 (95% CI: 0,648 – 2,20), p=1,00). Conclusion. There was no correlation between the accuracy of antibiotics treatment in CAP based on Gyssens method with clinical response of the patients.